HOW TO IMPROVE GENERATION Z'S MOTIVATION TO LEARN ENGLISH THROUGH ENGLISH CLUB - Mulyani, Yani Sri; Taufik Wibisono; Yesti Siti Nurjanah (Journal of Innovation Research and Knowledge, 2024)
The study aims to enhance the motivation of Generation Z to learn English through the English Club. The English Club is chosen as a means to create an environment that supports and motivates students to study English actively and continuously. The study was conducted using participatory and qualitative methods, involving students from the University of BSI Campus City of Tasikmalaya who are members of the English Club. The results of the study showed increased motivation for learning English in students who are actively engaged in the English club. Implications of this research can be used as a basis for the development of extra-curricular activities at the Bina Sarana Informatika University to improve the motivation to learn English in Generation Z.